ANALYSIS OF INTERNAL CONTROL COSO THE FUND MANAGEMENT ZAKAT, INFAQ AND SHADAQAH (ZIS) (A Case Study Foundation Social Fund Al-Falah branch of Jember) - Siti Maria W and Siska Putri I (Analisa: Journal of Social Science and Religion, 2015)
Accountability is often required community of a public institution. Community felt the need to know the flow of funds and the performance of the institution. LAZ and BAZ interested in reporting funds are transparent in order to maintain public trust and its existence by implementing internal control as well. Own internal control policies and procedures are used in operating activities to provide reliable information and ensure compliance with applicable laws or regulations in an organization. Internal control is absolutely necessary in an organization to avoid fraud and is used to ensure the effectiveness and efficiency of resources in order to avoid the loss or waste so that optimal utilization of funds. In addition, internal control is useful in preventing deviations from the implementation of activities as well as corrective actions when deviations have occurred. The purpose of this study was to investigate the application of internal control over management of funds, identify the strengths and weaknesses related to internal control is  applied,  and provide recommendations on the implementation of internal control systems in the Foundation fund management Social Fund Al-Falah branch of Jember. The method used is descriptive qualitative method and the object of the study is the management of the fund's internal control procedures. This study analyzed the internal control in accordance with the internal control components according to COSO and weaknesses found in internal control Foundation Social Fund Al-Falah branch of Jember. The conclusion is that internal control over existing   fund management activities on Yayasan Social Fund Al-Falah branch of Jember have some weaknesses, but overall control has been operating effectively.